Survei Ketrampilan Dasar Bermain Tenis Meja pada Mahasiswa Penjaskesrek Angkatan 2021 - Hace S.N Letsoin; M.D Hukubun; J. Solissa (Journal on Education, 2023)
This research is a single variable, namely a test of basic technical skills in playing table tennis for students of the Physical and Health Study Program class of 2021. The research in this research is a quantitative study in which the authors want to know the test of basic technical skills in playing table tennis for students of the Physical and Health Study Program class of 2021. The method in this research is a quantitative method the population used in this study is 80 samples in this study are 40 people variable in this study is a single variable instrument in this study measurement instrument through several test items service test, block test, push test, forhand test based on initial test results and the final test which is processed into data is processed using a statistical formula, so testing the hypothesis in this study can be proven that there are playing skills in Physical Education and Health and Recreation students class of 2021.